Hypoxia Induces Galectin-1 Expression Via Autoinduction of Placental Growth Factor in Retinal Pigment Epithelium Cells - Yamamoto, Taku; Kanda, Atsuhiro; Kase, Satoru; Ishida, Susumu (Investigative ophthalmology & visual science, 2021)
Galectin-1/LGALS1, a β-galactoside-binding protein, contributes to angiogenesis and fibrosis in various ocular diseases. Hypoxia-dependent and -independent pathways upregulate galectin-1/LGALS1 expression in Müller glial cells. Here, we present novel findings on the galectin-1/LGALS1 regulatory system in human retinal pigment epithelium (RPE) cells, the major cellular participant in the pathogenesis of neovascular age-related macular degeneration (nAMD). Human RPE cells were used to evaluate changes in gene and protein expression with real-time quantitative PCR and immunoblot analyses, respectively. The promoter and enhancer regions of LGALS1 were analyzed by reporter assay and chromatin immunoprecipitation. Immunofluorescence analysis of nAMD patient specimens was used to confirm the in vitro findings. Hypoxia induced galectin-1/LGALS1 expression via binding of hypoxia-inducible factor 1α (HIF-1α) to hypoxia-responsive elements in the LGALS1 promoter region. Blockade of vascular endothelial growth factor receptor 1 (VEGFR1) partially decreased hypoxia-induced galectin-1/LGALS1 expression. Among several VEGFR1 ligands induced by hypoxia, placental growth factor (PlGF)/PGF alone upregulated galectin-1/LGALS1 expression via phosphorylation of activator protein 1 (AP-1) subunits following AKT and p38 mitogen-activated protein kinase (MAPK) activation. An AP-1 site in the LGALS1 enhancer region was required for PlGF-induced galectin-1/LGALS1 expression in RPE cells. PlGF application upregulated PGF expression via extracellular signal-regulated kinase 1 and 2, AKT, and p38 MAPK pathways. nAMD patient specimens demonstrated co-localization of galectin-1 with HIF-1α, PlGF, and VEGFR1 in RPE cells. Our present findings implicate the significance of hypoxia as a key inducer of galectin-1/LGALS1 in RPE cells and the autoinduction of hypoxia-induced PlGF as a vicious cycle amplifying the pathogenesis of nAMD.